2021
DOI: 10.3389/fimmu.2021.601954
|View full text |Cite
|
Sign up to set email alerts
|

Cross With Caution: Antibiotic Cross-Reactivity and Co-Reactivity Patterns in Severe Cutaneous Adverse Reactions

Abstract: Current understanding of cross-reactivity in severe cutaneous adverse reactions to beta-lactam antibiotics is limited, thereby making recommendations for future prescribing difficult. The underlying immunopathogenesis of these reactions is not completely understood but involves interactions between small molecule drugs, T cells and HLA molecules. Historically, these reactions were considered to be specific to the inciting antibiotic and therefore likely to have minimal cross-reactivity. We assessed patients pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…As the main immune checkpoint inhibitors, PD-1 monoclonal antibodies have definite efficacy for various of solid tumors, but sometimes induce adverse skin reactions. 19 A study that included 2016 cases of camrelizumab (a PD-1 monoclonal antibody) monotherapy or combination therapy for advanced cancer showed that 834 of 1059 patients (78.8%) receiving camrelizumab monotherapy developed reactive cutaneous angiogenesis, 20 with an extremely high incidence. Recently, with the popularity of biologics and small-molecule drugs for the treatment of malignant tumors, reactive hyperplasia of the capillary endothelium has become more common, attracting the attention of otolaryngologists and dermatologists.…”
Section: Discussionmentioning
confidence: 99%
“…As the main immune checkpoint inhibitors, PD-1 monoclonal antibodies have definite efficacy for various of solid tumors, but sometimes induce adverse skin reactions. 19 A study that included 2016 cases of camrelizumab (a PD-1 monoclonal antibody) monotherapy or combination therapy for advanced cancer showed that 834 of 1059 patients (78.8%) receiving camrelizumab monotherapy developed reactive cutaneous angiogenesis, 20 with an extremely high incidence. Recently, with the popularity of biologics and small-molecule drugs for the treatment of malignant tumors, reactive hyperplasia of the capillary endothelium has become more common, attracting the attention of otolaryngologists and dermatologists.…”
Section: Discussionmentioning
confidence: 99%